2011
DOI: 10.21082/ijas.v12n2.2011.57-62
|View full text |Cite
|
Sign up to set email alerts
|

EX VITRO ROOTING OF OIL PALM (Elaeis guineensis Jacq.) PLANTLETS DERIVED FROM TISSUE CULTURE

Abstract: Plantlets of oil palm (Elaeis guineensis Jacq.) derived from somatic embryos sometimes do not form well developed-roots. Root formation of unrooted-plantlets can be induced with auxin during ex vitro acclimatization period to simplify the procedure and to reduce seedling production cost. Experiments were conducted using a completely randomized design to determine the effect of different types of auxin, i.e. indole-3-acetic acid (IAA), indole-3-butyric acid (IBA), and 1-naphthalene-acetic acid (NAA) at differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
1
6
0
3
Order By: Relevance
“…Shekafandeh [12] observed increased rooting frequency and number of roots from zero percent in untreated shoots to 91.7% and 3.3 roots per shoot, respectively, when the basal end of the shoots were dipped in a solution of 1.5 mg/l IAA and 0.3 mg/l IBA for 24 h before culturing in soil mixture in Myrtle (Myrtus communis L.) plant. Similar results were also reported by Sumaryono and Riyadi [20] guineensis Jacq.). These results indicated the significance of treating of microshoots with plant growth regulators during ex vitro rooting before culturing in soil medium.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Shekafandeh [12] observed increased rooting frequency and number of roots from zero percent in untreated shoots to 91.7% and 3.3 roots per shoot, respectively, when the basal end of the shoots were dipped in a solution of 1.5 mg/l IAA and 0.3 mg/l IBA for 24 h before culturing in soil mixture in Myrtle (Myrtus communis L.) plant. Similar results were also reported by Sumaryono and Riyadi [20] guineensis Jacq.). These results indicated the significance of treating of microshoots with plant growth regulators during ex vitro rooting before culturing in soil medium.…”
Section: Resultssupporting
confidence: 90%
“…Similarly, Martin [16] obtained an average of 5.6 roots per shoot after the microshoots of Rotula aquatica Lour were dipped in 0.5 mg/l NAA for 25 days. Biradar et al [20] found best root formation on shoot treated with 2 mM NAA with 80% rooting frequency in oil palm. However, other authors Martin [22] and Chinnu [23] obtained best result of ex vitro rooting by using IBA.…”
Section: Resultsmentioning
confidence: 98%
“…Tinggi planlet kelapa kopyor yang digunakan oleh Sisunandar (2011) saat aklimatisasi antara 19 sampai 21 cm, sesuai dengan tinggi planlet terbaik pada penelitian ini yakni lebih dari 20 cm. Ukuran planlet awal juga berpengaruh terhadap daya tumbuh tanaman palma lain seperti pada kurma (Phoenix dactylifera) tinggi planlet terbaik antara 12-15 cm (Abahmane, 2011;Darwesh, 2015), planlet pejibaye atau peach palm (Bactris gasipaes) lebih dari 6 cm (Steinmacher et al, 2007), dan planlet kelapa sawit (Elaeis guineensis) lebih dari 9,5 cm (Sumaryono & Riyadi, 2011) atau lebih dari 6 cm (Thuzar et al, 2011).…”
Section: Pengaruh Tinggi Awal Planletunclassified
“…Sedangkan pada kurma, planlet yang telah memiliki 2-3 daun terbuka dan lurus digunakan sebagai salah satu standar planlet kurma siap untuk diaklimatisasi (Abahmane, 2011;Darwesh, 2015). Planlet dengan 2-3 helai daun terbuka juga merupakan kriteria pada planlet kelapa sawit untuk diaklimatisasi (Sumaryono & Riyadi, 2011).…”
Section: Pengaruh Jumlah Daun Dan Diameter Planletunclassified
See 1 more Smart Citation